Ultimate job search : master the art of finding your ideal job, getting an interview and networking - Williams, Lynn, 1955 January 15- (Kogan Pages, 2018)
"A one-stop shop for all job hunters, this fifth edition of Ultimate Job Search takes the stress out of job hunting and provides advice on every stage of the process including: preparing a poweful CV that will get you noticed ; sample cover letters and emails that are really persuasive ; making a great impression at interviews ; dealing with offers and rejections in a positive manner."--Back cover.